Assessment of Lifestyle Experiences across Lifespan and Cognitive Ageing in the Indian Context. (September 2020) - Paplikar, Avanthi; Ballal, Divya; Varghese, Feba; Sireesha, Jala; Dwivedi, Ramya; Rajan, Amulya; Mekala, Shailaja; Arshad, Faheem; Kaul, Subhash; Alladi, Suvarna
With rising numbers of elderly and dementia in developing societies, there is a need to understand factors protective against dementia. Evidence suggests that lifetime cognitive activities including education, occupation, and complex leisure activities contribute to cognitive reserve. However, these factors are understudied in India. This paper describes the validation of the Lifetime of Experiences Questionnaire (LEQ), a comprehensive measure of complex lifetime activities, to the Indian cultural context. It also examines the relationship between lifetime experiences and cognition among 52 healthy elderly and 30 dementia patients. High inter-rater (κ=0.923, p < 0.001), test-retest (ρ: 0.905 to 0.986) reliability, and internal consistency were found for LEQ-total (0.992) and sub-scores. Literate dementia patients (25) scored significantly lower mid-life (27.5 vs. 23.3), late-life (28.5 vs. 22.5) and total LEQ (83.5 vs. 20.9) scores than literate healthy group (37). LEQ scores positively correlated with global cognition, and domains of attention and memory on the Addenbrooke's Cognitive Examination, in healthy and dementia groups. Moreover, LEQ scores correlated positively with age at onset of dementia and negatively with clinical dementia rating (CDR) scores. Our study demonstrates that lifetime activities, especially mid-life experiences, play a protective role in development of late-life dementia, and need to be advocated to preserve late-life cognition.